Curbing precarious informal employment: A case study of precarious workers in the South Korean construction industry - Aelim Yun (International Labour Organization (ILO), 2017)
The construction industry in Korea is characterized by a complex pyramid structure comprised of one main construction company ('main contractor') and several layers of subcontractors. The prevailing form of employment relationship is informal and indirect employment via intermediaries or foremen. Construction workers are hired only for the period of a certain construction project. The number of economically dependent construction workers also rapidly increased since the late 1990s. This case study focuses on the strategies of the Korean trade unions in their fight for precarious workers' rights. Since 2000, the Korean Federation of Construction Industry Trade Unions (KFCITU) has carried out an organizing campaign in construction sites. The campaign included the signing of a collective agreement between the local unions and site managers of the main contractors. Union organizers carried out propagation activities at construction sites, and took advantage of the OSH regulations to talk main contractors into collective bargaining. The KFCITU has also organized workers in construction equipment trade. For example, tower crane operators formed an affiliated union, and went on a general strike for 28 days in 2001, and as a result, concluded a collective agreement with the cooperative of tower crane operation companies. Thereafter, the union attained, for the very first time at construction sites, Sundays off work in 2003, an eight-hour workday in 2007, and a 40-hour workweek in 2009, through collective bargaining. It is also noteworthy that the unionization of 'owner-operators', who are usually regarded as self-employed, has increased. The unionization of concrete mixer truck drivers in 2000 was followed by dump truck drivers in 2004, and later on by excavator operators in 2007. The unionization of precarious workers was built up on a common discontent with their working conditions, the social network across a workplace level, the voluntary fight by the rank-and-file, and the effective support from the existing trade unions. It is the organizing strategy based on labour market interests and the pursuit of multi-employer bargaining beyond an enterprise. The union has also tried to make user-enterprises acknowledge the position of an 'employer' who is responsible for workers' rights. The distinctive feature of this case exists in the union's strategy for reversing the risk-and-insecurity transfer chain for all workers, irrespective of employment status.
Keywords: 330